Association of cannabis and/or opioid with quality of life and healthcare utilization in patients with chronic pain - Salmasi, Vafi; Nelson, Lorene M.; Hong, Juliette; Mackey, Sean C. (Frontiers in Pain Research, 2022)
Background Opioids have been commonly used to treat chronic pain, but they are associated with significant morbidity and mortality. Cannabis has been advocated as an alternative; however, a growing number of patients are now using a combination of opioid and cannabis and the impact of this combination is not well-studied. Aim We characterized use of opioid and/or cannabis in patients with chronic pain; and compared utilization of healthcare resources. Methods We conducted a cross-sectional study to determine if measures of physical, psychological and social functioning differed among patients according to whether they used opioids and/or cannabis. We used our learning healthcare system – CHOIR – to capture NIH Patient Reported Outcomes Measure Information System surveys, and legacy pain and treatment specific questions. Results Patients who report use of opioid and/or cannabis experience higher levels of physical, psychological and social distress. After adjusting for inversed weight of propensity scores, they have higher odds of visiting an emergency room, staying overnight at the hospital, and visiting a physician. Conclusion Our results show that use of opioid and/or cannabis is associated with worse baseline characteristics and outcomes. Our study however cannot determine if worse outcomes are due to the opioids and/or cannabis or simply that these patients are worse off before using opioids and/or cannabis. Thus, it is important to characterize the trajectory of these patients in a prospective longitudinal study.